Preliminary experience of tigecycline treatment in critically ill children with ventilator-associated pneumonia. Issue 1 (January 2020) - Lin, Shupeng; Liang, Lingfang; Zhang, Chenmei; Ye, Sheng
Objective: Ventilator-associated pneumonia (VAP) is a life-threatening complication for children who are treated in a paediatric intensive care unit. Tigecycline treatment of children with VAP has not been well studied. This study aimed to describe tigecycline use in children with VAP in a tertiary care hospital. Methods: We conducted a retrospective chart review in a tertiary hospital from May 1, 2012 to May 1, 2017. Results: Twenty-four children (20 girls) with median age of 8 months (range, 27 days to 6 years and 9 months) were treated with tigecycline. In-hospital mortality was 41.7% (10/24). The primary diagnosis was congenital heart disease (15/24). A total of 70.8% (17/24) of patients received a loading dose (1.5 mg/kg), followed by 1 mg/kg every 12 hours. The median duration of tigecycline therapy was 10.75 days (range, 3–21.5 days). Sulperazone was the most frequently used concomitant antibiotic. Eighteen pathogens were isolated in 16 cases. Tigecycline therapy failed in 41.6% (10/24) of patients and 20.8% (5/24) died. The pathogen was eradicated in 37.5% (6/16) of patients. No serious adverse effects were detected. Conclusion: Tigecycline combined with other agents as salvage therapy in children with VAP is well tolerated. Our preliminary results show a positive clinical response.